Genome-Wide Identification of MAPK, MAPKK, and MAPKKK Gene Families in Fagopyrum tataricum and Analysis of Their Expression Patterns Under Abiotic Stress - Wang, Zhen; Yan, Song; Ren, Weichao; Liu, Yan; Sun, Wei; Liu, Meiqi; Lu, Jiaxin; Mi, Yaolei; Ma, Wei (Frontiers in Genetics, 2022)
The mitogen-activated protein kinase (MAPK) cascade is an extremely highly conserved signal transduction pathway, ubiquitous in eukaryotes, such as animals and plants. The MAPK cascade has a dominant role in regulating plant adaptation to the environment, such as via stress responses, osmotic adjustment, and processes that modulate pathogenicity. In the present study, the MAPK cascade gene family was identified in Fagopyrum tataricum (Tartary buckwheat), based on complete genome sequence data. Using phylogenetic tree, conservative motif, and chromosome location analyses, a total of 65 FtMAPK cascade genes, distributed on five chromosomes, were classified into three families: MAPK (n = 8), MAPKK (n = 1), and MAPKKK (n = 56). Transcriptome data from Tartary buckwheat seedlings grown under different light conditions demonstrated that, under blue and red light, the expression levels of 18 and 36 FtMAPK cascade genes were up-regulated and down-regulated, respectively. Through qRT-PCR experiments, FtMAPK5, FtMAPKK1, FtMAPKKK8, FtMAPKKK10, and FtMAPKKK24 gene expression levels in Tartary buckwheat seedlings were shown to increase under three types of abiotic stress: drought, salt, and high temperature. A co-expression network of FtMAPK cascade genes was constructed, based on gene expression levels under different light conditions, and co-expressed genes annotated by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses, which identified numerous transcription factors related to plant abiotic stress. We conclude that FtMAPK cascade genes have important roles in the growth and development of Tartary buckwheat, as well as its responses to abiotic stress.